Diagnóstico de coccidiosis por Eimeria spp. en bovinos menores de un año, del municipio de Sotaquirá, Boyacá (2022)
Eng: In bovine milk production, coccidiosis due to Eimeria spp. It brings with it great economic impacts due to the productive losses generated, both in asymptomatic and symptomatic individuals, therefore, this parasitosis increases production costs, placing this infectious disease as one of the most important in bovine production. Due to this, the main objective of this study was to diagnose Coccidiosis due to Eimeria spp. In cattle under one year old, from the municipality of Sotaquirá, Boyacá, a sample size of 339 individuals was taken. These samples were processed using the Formol ether or modified Ritchie diagnostic technique, and the results were processed using the EpiInfo® statistical program. A general prevalence of 92.63% was obtained, with individuals <6 months and the Holstein breed being the most prevalent. In addition, there was a statistical association with the presence of other species, diarrhea, and deworming for Eimeria spp infection. with values <0.05, with the presence of other species (RP=1.3949) and diarrhea (RP=1.3778) as possible risk factors, while deworming as a possible protection factor (RP=0.9125), through the analysis of the logistic regression, diarrhea is the only risk factor (P= 0.011 and OR=4.11), it is concluded that the importance of this type of investigative studies lies in the fact that it seeks to control coccidia caused by Eimeria spp. to reduce economic losses in the sector, and make bovine production more profitable.